THE INFLUENCE OF LISTENING SONG TOWARD STUDENTS’ PRONUNCIATION ABILITY AT THE ELEVENTH GRADE STUDENTS OF SMA MUHAMMADIYAH 2 METRO - Andianto - Andianto (Premise: Journal of English Education and Applied Linguistics, 2013)
The objective of the research is to examine whether there is a significant influence of listening song towards students’ pronunciation ability at the eleventh grade students of SMA Muhammadiyah 2 Metro. The method applied in this research was an experimental study. It was conducted at the eleventh grade students of SMA Muhammadiyah 2 Metro which contains two classes. The Sample is XI IPA chosen by using cluster random sampling. The data were analyzed by using independent T test (SPSS 17). Based on the data analysis, there is a research finding that can be drawn as “there is a significant influence of listening toward students’ pronunciation ability. Listening song can give a positive effect toward students’ pronunciation ability.